Implementatiion of engine control stretegies with electronics : SP-477 (Detroit section, Junior activity Spring Lecture ;, 1980)
Control of the homogeneous. Charge passenger. Car engine. Defining the problem - Microprocessor design considerations - Ford´s 1980 central fuel injection system - An interactive approach to electronic engine controls at Ford Motor Company - GM Micro-computer engine control system.